White mulberry: a forest feast for birds and nature’s healing treasure / Mohd Izani Othman - Othman, Mohd Izani (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In the heart of the forest, where nature's wonders flourish, a remarkable tree stands tall and offers a delectable treat to both animals and humans alike. white mulberry (Morus alba) is a species that not only attracts a diverse array of avian friends with its sweet and juicy fruits but also holds medicinal properties that have been treasured for centuries. It can be found in temperate and subtropical parts of Asia, the Americas, Europe, and Africa, and is a member of the Moraceae family. Let us delve into the enchanting world of white mulberry, where the forest, animals, and its healing powers intertwine. A bounty for the feathered residents and silk industry White mulberry trees are not only cherished by birds but also play a vital role in supporting avian diversity within the forest ecosystem. The irresistibly sweet and juicy fruits of white mulberry attract songbirds and fruit-eating species, turning these trees into bustling hubs of avian activity. As the birds’ flock to indulge in the delicious bounty provided by white mulberry, they contribute to a vibrant and thriving ecosystem within the forest.